Colección y evaluación agronómica de cultivares de fréjol guiador de clima temperado en la Argelia, Loja - Correa Pardo, Gloria Omayra (2014)
This research was conducted at the Experimental Teaching Farm “La Argelia " , from August 2012 to September 2013 to contribute towards the conservation and improvement of climbing beans via collection and agronomic characterization. The selection of promising material was used to increase the Agricultural Area Germplasm Bank. Initially we proceeded to collect 20 cultivars of climbing beans in the following districts: Saraguro, Celica, Gonzanamá, Quilanga, Espindola, Loja, and Paltas. Then we proceeded to conduct an analysis of purity and viability of the seeds to determine their quality. For the agronomic characterization of the cultivars collected, was installed under a trellis support system, with 16 lines of Phaseolus vulgaris and Phaseolus coccineus L. 4, distributed in a randomized block design with 20 treatments and three replicates in total 60 experimental units. Upon analysis of the results it was established that the earliest flowering cultivars were the Phaseolus vulgaris L., ranging from 53 to 97.33 days to flowering; while the tardiest flowering cultivars were the Phaseolus coccineus L. species with a range of from 111 to 139.33 days to blossoming. Regarding the number of flowers per plant, and number of flowers per cluster the Phaseolus coccineus L. cultivar presented the highest average; however this species had the lowest number of seeds per pod, due to their large size. The accessions of Phaseolus vulgaris L., displayed a higher number of seeds per pod which is consistent with the smaller size of the same. At the end of the field study it was possible to increase the Agricultural Area Germplasm Bank with a seed sample of each of the obtained cultivars . Finally it was concluded that in the province of Loja a variability of climbing beans exist, primarily in the species Phaseolus vulgaris L. and Phaseolus coccineus L. and the districts from where the largest number of accessions were collected, namely Loja and Saraguro.